Caring for Children Diagnosed with Autism Spectrum Disorder: Caregivers’ Experiences - Mazibuko, Nomfundo; Shilubane, Hilda; Manganye, Solomon (Africa Journal of Nursing and Midwifery, 2020)
Although awareness about autism has increased in developed countries, more so than in developing countries, autism spectrum disorder (ASD) remains poorly understood by most South Africans, especially those in remote areas and in areas where research is limited. Furthermore, intervention services are often scarce or not available due to lack of knowledge amongst healthcare professionals. The current study aimed to explore caregivers’ experiences of children with ASD in the Ehlanzeni District, Mpumalanga, South Africa. The study adopted a qualitative approach, and data was collected using semi-structured interviews, in which an interview guide was used. Twelve participants were selected purposively from the three different schools in the Ehlanzeni District and interviewed for the study. The data was analysed using thematic content analysis. The study adhered to ethical considerations. The findings of the study indicated that caregivers of children diagnosed with ASD experienced psychological stress; social stress; financial burden; lack of family support; and reported unavailability and accessibility of services. Therefore, information regarding a range of inexpensive interventions and educational programmes should be available for caregivers in order to reduce their psychological and social stress. Medicines should be available and accessible within the district to avoid caregivers having to travel long hours to access them, and to reduce their financial burden. Caregivers’ support groups should also be established.